Speed limits in the mantle of Southeast Asia and Southern China - Zaets, L. N. (Geofizicheskiy Zhurnal, 2011)
This work is concerned with distinguishing and analysis of mantle velocity boundaries under the structures of the region studied and their correlation with the surface structures within the developed 3 D P-velocity model of the mantle under Southeast Asia and South-China platform. 3 D P-velocity model has been obtained as a result of application of the method of Taylor approximation of solution of seismic tomography of P-waves arrival time introduced by V.S. Geiko.